Indonesia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Indonesia during 1994-96. Following the easing of domestic demand pressures, the focus of monetary policy shifted in early 1993/94 to supporting economic growth, as concerns developed over an incipient weakening of export performance and output. At the same time, the fiscal position was strengthened. Reflecting the strong growth in non-oil/gas revenue, the overall central government deficit, excluding oil/gas revenue, declined by 2 percentage points of GDP. With the shift in monetary policy, interest rates declined rapidly, and there was a strong pickup in credit to the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet